2011
DOI: 10.19030/iber.v5i2.3454
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Of Short-Term Volatility Accentuation Within The Trading Day: An Investigation Of The U.S. And European Equity Markets

Abstract: Trading friction leads into accentuated stock price volatility over the short term. As such, short-term accentuated volatility can be viewed as symptomatic of a market with increased inefficiencies in the price discovery process. If price discovery is marked by price swings, runs and reversals, then short period (intra-day) volatility is heightened in that market. In this study, we use return series with various differencing intervals that are as short as half-hour and as long as two weeks to investigate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Especially for the London Stock Exchange, opening and closing volatility is particularly more accentuated on Mondays and Fridays respectively. This result is consistent with Ozenbas (2006) where it is reported that the London Stock Exchange has the most pronounced U-shaped intra-day pattern of volatility among the same markets studied.…”
Section: Empirical Methodology and Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Especially for the London Stock Exchange, opening and closing volatility is particularly more accentuated on Mondays and Fridays respectively. This result is consistent with Ozenbas (2006) where it is reported that the London Stock Exchange has the most pronounced U-shaped intra-day pattern of volatility among the same markets studied.…”
Section: Empirical Methodology and Resultssupporting
confidence: 92%
“…Intra-day patterns in volatility, and volume were first documented by Wood, McInish and Ord (1985), Jain and Joh (1988) and Harris (1986). Subsequently, this area has been investigated by other academic studies including Madhavan et al (1997) and Ozenbas (2006). Generally, these studies find a U-shape in volume and volatility across the markets studied.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A study of volatility patterns in the five markets included in the current study can be found at Ozenbas (2006).…”
Section: Empirical Methodology and Resultsmentioning
confidence: 99%
“…For instance, Ozenbas (2006) shows that opening half-hour volatility in the London Stock Exchange is extremely accentuated, it is more than 3 times the average mid-day volatility. On the other hand, volume in the morning period in this market is the lowest among the five markets studied.…”
Section: Empirical Methodology and Resultsmentioning
confidence: 99%
“…Similar findings were provided by Harju and Hussain (2006) who asserted that the European Indices FTSE 100, XDAX30, SMI and CAC40 followed a reverse J pattern which differed slightly to an L pattern. Also, Ozenbas (2006) asserted that the same was true for NASDAQ and NYSE, as well as, for the London Stock Exchange, the Deutsche Boerse and Euronext. In contrast to these findings, Syed Mujahid Hussain (2008) found a J shaped pattern in the DAX, for the period [2004][2005].…”
Section: Past Literaturementioning
confidence: 88%